Composition and characterization of simulated putrescible garbage - Dasgupta B.; Upender S.; Mondal M.K. (My University, 2025)
The composition and characterization of liquidised garbage (LG) during liquidisation process were carried out to access various properties, viz., moisture, organics, ash, elemental composition, suspension stability, flow characteristics, higher heating value (HHV), glucose and total organic carbon (TOC) for getting preliminary information about liquidisation as a pre-treatment process for anaerobic digestion of simulated garbage (SG). Minimum moisture and maximum organic content were found as 750 and 850 g kg-1, respectively. From elemental analysis, C/N ratio obtained was suitable for the growth of microbes. The HHV of dried solid phase for LG at 393 K was higher than that of mechanically ground garbage (MEC). The LG was regarded as a pseudo plastic liquid from values of flow behaviour index obtained. The amount of glucose was found to be decreased during liquidisation process. The amount of TOC in both solid and liquid phase of LG was more as compared to MEC. © 2011 Elsevier Ltd.